Prenatal Diagnosis of Adrenal Neuroblastoma: A Case Report with a Brief Review of the Literature. (27th March 2013) - Erol, Onur; Süren, Dinç; Büyükkınacı Erol, Melek
Abstract : A case of adrenal cystic neuroblastoma detected at 37 weeks of gestation is reported. Postnatal ultrasonographic examination showed slightly increased in size demonstrating marked septations within the cyst. After the tumor was resected, histopathological examinations confirmed the diagnosis. The patient is developing normally at 1 year of age.